Does a New Modification of the Two-Step Injection Technique for Inferior Alveolar Nerve Block Reduce Pain Compared to the Conventional Technique? A Randomized Clinical Trial - Amirhossein Moaddabi; Alessandra Valletta; Mohammad Koochek Dezfuli; Parisa Soltani; Saeedeh Ebrahimikiyasari; Abolfazl Hosseinnataj; Kioumars Tavakoli Tafti; Gianrico Spagnuolo (Hindawi Limited, 2023)
Background. The ability to control pain is an essential part of dental procedures and the need for optimal pain control and reduction of discomfort is the primary concern of every dentist. This study aims to compare the pain and vital signs during inferior alveolar nerve block between conventional and a new modification of the two-step injection techniques. Methods. In this institutional single-blind randomized clinical trial, attendees of dental school at Mazandaran University of Medical Sciences from February to May 2022 were included. Inclusion criteria were 20-60 years old and healthy (ASA1) individuals who were willing to participate in this study. Individuals who were taking medications affecting their understanding of pain and patients with active infections at the injection site were excluded. These individuals were divided into two groups. First, superficial anesthesia was performed and afterward, conventional and two-step injection techniques were performed. For the two-step injection method, 6 mm of the needle was injected into the mucosa and one-third of the local anesthetic solution was released from the computer-controlled injection toolkit. Afterward, a 25 mm 30-gauge needle was reinserted into the previous hole delivering the remaining local anesthetic. The pain during injection was measured by a patient-reported numerical rating scale (NRS). Moreover, vital signs were monitored immediately before and after the injection. Kolmogorov-Smirnov test, Mann-Whitney U test, independent T-test, and Fisher's exact χ2 test were performed for statistical analysis (α = 0.05). Results. This study involved 32 adults aged between 20 and 50 years old with 1 : 1 female/male sex distribution. The pain score was significantly higher in the conventional injection technique compared to the two-step injection technique in all sex and age groups. There were no significant differences in vital signs between the conventional and two-step injection techniques. There was no significant difference in the mean pain scores of females and males, regardless of their injection techniques. Conclusion. Utilizing the two-step injection technique in patients for inferior alveolar block reduces pain during injection without altering patients' vital signs significantly. This trial is registered with IRCT20220106053646N1.